American Association of Nurse Practitioners National Nurse Practitioner sample survey: Update on acute care nurse practitioner practice. Issue 3 (March 2018) - Kleinpell, Ruth; Cook, Michelle L.; Padden, Diane L.
ABSTRACT: Background and purpose: Data from national surveys on the practice of nurse practitioners (NPs) provides valuable information on aspects of practice, demographic characteristics of providers and patients, plans for continued employment, and role satisfaction. The American Association of Nurse Practitioners (AANP) has been conducting the AANP Sample Survey since 1988. Methods: The most recent AANP Sample Survey was conducted in 2016 with a random stratified survey of 40, 000 NPs. Data were collected bimodally, by internet and mail surveys. Responses were received from 3, 970 respondents (9.9% response rate), with 335 respondents reporting NP certification in acute care as adult-gerontology acute care and/or pediatric acute care. Results: Almost all acute care nurse practitioners (ACNPs) reported that they were clinically practicing in 2016 (99.3%), with the top three areas encompassing cardiovascular (20.5%), critical care (12.1%), and hospitalist roles (6.3%). More than 1 in 4 ACNPs worked in a hospital inpatient setting, with 16.1% reporting work in a hospital outpatient clinic, 7.7% in a private group practice, 6.5% at a public university, and some in combined roles covering both inpatient and outpatient care, or on consultation service or specialty-based teams. On average, 34.1% of the patients ACNPs saw were between the ages of 66 and 85 years, and 11.2% were 85 years and older. The top 3 medication classes in which ACNPs regularly prescribe were diuretics (31.9%), analgesic narcotics (31.2%), and antibiotics (27.3%). Majority (88%) report satisfaction with the role, and approximately one third (31.1%) expect to continue to work in their current practice for more than 10 years. Implications for practice: The findings of the 2016 AANP National NP Sample Survey data related to ACNP practice identify expansion of work settings, practice consistent with acute care scope of practice, role satisfaction, and intent to continue working. Continued monitoring of practice components and employment is indicated to track ACNP workforce trends.